2006
DOI: 10.1200/jco.2006.24.18_suppl.14040
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of PS-341 (bortezomib) with or without irinotecan in patients (pts) with advanced gastric adenocarcinomas (AGA)

Abstract: 14040 Background: We are conducting a phase II trial of the proteasome inhibitor, PS-341, with or without irinotecan in pts with AGA. The combination of PS-341 and irinotecan has been studied in preclinical tumor models including a murine xenograft model of colon cancer, where the combination achieved significantly more tumor shrinkage than either agent alone. The primary objective of this study is to determine response rates, toxicities, progression-free survival, and overall survival in pts with AGA receivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Although this study focused on gastric cancer cell lines, not esophageal, the adjacency of these two organs coupled with established similar treatment approaches suggest these data are in fact relevant even to the latter. Third, favorable, mounting clinical evidence in patients with other solid tumor malignancies suggests that this agent merits further study in patients with esophageal cancer [7,8,9]. Ocean and others treated 36 gastric cancer patients with bortezomib alone versus bortezomib plus irinotecan [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this study focused on gastric cancer cell lines, not esophageal, the adjacency of these two organs coupled with established similar treatment approaches suggest these data are in fact relevant even to the latter. Third, favorable, mounting clinical evidence in patients with other solid tumor malignancies suggests that this agent merits further study in patients with esophageal cancer [7,8,9]. Ocean and others treated 36 gastric cancer patients with bortezomib alone versus bortezomib plus irinotecan [7].…”
Section: Introductionmentioning
confidence: 99%
“…Third, favorable, mounting clinical evidence in patients with other solid tumor malignancies suggests that this agent merits further study in patients with esophageal cancer [7,8,9]. Ocean and others treated 36 gastric cancer patients with bortezomib alone versus bortezomib plus irinotecan [7]. The latter regimen yielded a 44% response rate, and the former a 9% response rate.…”
Section: Introductionmentioning
confidence: 99%
“…The cohort of patients treated with the combination presented significant activity with a PR rate of 28% and a median PFS of 3.5 months, whereas in patients treated with bortezomib alone the RR was 0% and the median PFS 1.4 months. 75 The preliminary results from gene profile analysis of eight paired tumor samples showed that the expression of 643 genes significantly changed after bortezomib treatment and 42% of the genes changed by Ն twofold between pretreatment and on treatment. The pathways that were significantly upregulated and downregulated were the apoptotic, PI3K and MAPK signaling pathways.…”
Section: Apoptosis Promotersmentioning
confidence: 99%
“…The proteasome inhibitor Bortezomib (Velcade ® , PS-341; Janssen-Cilag Ltd., High Wycombe, U.K.) is proving valuable in the management of certain hematological malignancies, notably myeloma, and has encouraging preclinical and early clinical evidence of activity in solid tumors [67][68][69][70]. Phase I and II studies in CRC have included combination with 5-FU/LV, capecitabine, irinotecan, and FOLFOX [71,72]. However, the phase II trial with irinotecan in irinotecan-refractory CRC was halted because of poor activity.…”
Section: Proteasome Inhibitionmentioning
confidence: 99%